Validity of P-POSSUM in adult cancer surgery (PACS) - Sudipta Mukherjee; Ankit Kedia; Jyotsna Goswami; Arunangshu Chakraborty (Wolters Kluwer Medknow Publications, 2022)
Background and Aims: Objective prediction of postoperative morbidity and mortality can help clinicians for appropriate resource allocation and counseling of patients and their kin. Among different scoring systems, "Portsmouth- Physiological and Operative Severity Score for the enumeration of Mortality and Morbidity" (P-POSSUM) includes both preoperative and intraoperative parameters for postoperative risk prediction. The aim of this study was to investigate the validity of morbidity prediction by P-POSSUM in patients requiring intensive care after undergoing major surgeries for gastrointestinal and gynecological malignancies. Material and Methods: All adult patients (>18 years) undergoing gastrointestinal and gynecological cancer surgeries who were shifted to intensive care unit (ICU) or high dependency unit (HDU) for postoperative care were included and P-POSSUM was measured. Postoperative complications were graded as per Clavien-Dindo (CD) grading and have been compared with predicted complications as per P-POSSUM. Results: 143 patients were included in the study and the median P-POSSUM score was 35. The mean predicted morbidity was 55.28% (SD 25.54%) and the observed complications were 45.45%, which shows P- POSSUM has over predicted morbidity. At P-POSSUM values 60 and above, the incidence of major complications was 22.22%, compared to 6.25% for the rest (Odds ratio 4.286). Conclusion: P-POSSUM is not a reliable predictor of postoperative morbidity for patients undergoing major gynecological and gastrointestinal surgeries for cancer in our institution. But there is a significant incidence of major complications with P- POSSUM morbidity prediction score 60 or higher leading to the need for more stringent assessment and monitoring in that subgroup.